The Comparison of the Immunologic Properties of Stem Cells Isolated from Human Exfoliated Deciduous Teeth, Dental Pulp, and Dental Follicles. (6th December 2015) - Yildirim, Selin; Zibandeh, Noushin; Genc, Deniz; Ozcan, Elif Merve; Goker, Kamil; Akkoc, Tunc
Abstract : Aim . To compare the effects of various mesenchymal stem cells, those isolated from human exfoliated deciduous teeth (SHEDs), dental pulp stem cells (DPSCs), and dental follicle stem cells (DFSCs), on human peripheral blood mononuclear cells (PBMCs). Method . Mesenchymal stem cells were isolated from three sources in the orofacial region. Characterization and PCR analyses were performed. Lymphocytes were isolated from healthy peripheral venous blood. Lymphocytes were cocultured with stem cells in the presence and absence of IFN- γ and stimulated with anti-CD2, anti-CD3, and anti-CD28 for 3 days. Then, lymphocyte proliferation, the number of CD4 + FoxP3 + T regulatory cells, and the levels of Fas/Fas ligand, IL-4, IL-10, and IFN- γ in the culture supernatant were measured. Results . The DFSCs exhibited an enhanced differentiation capacity and an increased number of CD4 + FoxP3 + T lymphocytes and suppressed the proliferation and apoptosis of PBMCs compared with SHEDs and DPSCs. The addition of IFN- γ augmented the proliferation of DFSCs. Furthermore, the DFSCs suppressed IL-4 and IFN- γ cytokine levels and enhanced IL-10 levels compared with the other cell sources. Conclusion . These results suggest that IFN- γ stimulates DFSCs by inducing an immunomodulatory effect on the PBMCs of healthy donors while suppressing apoptosis and proliferation and increasing the number of CD4 + FoxP3 + cells.